Challenges in IPF diagnosis, current management and future perspectives - Wells, Athol U.; Costabel, Ulrich; Poletti, Venerino; Crestani, Bruno; Egan, Jim; Margaritopoulos, George; Antoniou, Katerina (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Recent developments have clarified our understanding of IPF and improved outcomes with two viable new therapeutic options, pirfenidone and nintedanib. In spite of these advances, questions and challenges concerning IPF still remain. Here we will focus on some of these unresolved areas: the diagnosis of IPF is hindered by limitations in current practice guidelines, surgical lung biopsy is contraindicated in many patients, the accuracy of prognostic evaluation needs to be increased and tolerability factors can jeopardise adherence to treatment. We will also identify new developments shaping the future of IPF management such as cryobiopsy, increased understanding of genetic factors and new treatment paradigms, which may help to fulfil currently unmet needs. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32; Suppl 1: 28-35)